STUDENT’S ERRORS IN WRITING RECOUN TEXT BY USING SIMPLE PAST TENSE AT THE THRID GRADE STUDENTS OF SMU NEGERI I SERDANG BEDAGAI - Marice Saragih (The Seall Journal, 2020)
The purpose of this research is to explain the types of grammatical errors made by the students in writing recount text, to explain what the causes of errors (omission, addition, misinformation, misordering) that students often do in writing recount text by using simple Past tense, to explain how to overcome the errors (omission, addition, misinformation, misordering) that students often do in the process of learning to write recount text by using simple past tense. This research used a qualitative design because this study deals with the data in form of numbers, and also to describe their past experiences in linguistic expression’s error that made by students. The place of research was at third grade students of SMU Negeri I Serdang Bedagai . The Population of the students are 56 students so that the researcher take the sample of the students are 28 which consist of boys and girls. In this case, the writer intended the specific data is the result of student error analysis in the use of simple past tense in writing recount text. The writer found a lot of errors in using the simple past tense in students’ recount writing, and then the writer made the classifying of the students’ error. After analyzing all the text, there were some findings that explained : the students made errors while they were learning about writing a recount text by using simple past tense. The errors divided into 4 errors they are : omission, addition, misinformation, and misordering. Based on the description of data analysis, there are 151 total number of errors that the third grade students of SMU Negeri I Serdang Bedagai already made, such as: 5 or (3,31%) omission errors which is made by the students, 91 or (60,26%) errors in addition, 51 or (33,77%) erors in misinformation and the last is 4 or (2,64%) errors in misordering. The writer concluded that the type of grammatical error done by the students is Simple Past Tense. It occured because of lack of understanding of students of simple past tense itself.